Minha Casa Minha Vida Program in Bauru: Equipment and collective services as one of the parameters to adequate housing and social sustainability - Menezes Junior, Marcos Antonio Santana; Salcedo, Rosio Fernández Baca (Technical and Scientific Journal Green Cities, 2022)
The Bauru Municipal Government, faced with the demand for Social Interest Housing in the city, implemented in 2009, in partnership with the Ministério das Cidades and the Caixa Econômica Federal (CEF), the Minha Casa Minha Vida Program (MCMVP), through the construction of 19 housing developments. In this sense, the objective of this study is to analyze the adequate housing from the relationship of housing developments of the Minha Casa Minha Vida Program (MCMVP) in the city of Bauru in relation to the supply of equipment and collective services and basic trade existing in the Context. The Methodology is based on architecture and dialog, in which two stages were defined. The first covers the Context in which the development is located, which will be analyzed according to the physical-geographical, architectural, urban and environmental parameters. The second stage, the Text: the MCMV housing developments and their relationship with the collective equipments and services and the local commerce, according to Prinz's parameters. The results show that, among the 19 residential developments analyzed in this study, none has access to all the collective equipment and services in full, because most of the residential developments do not have squares and parks nearby, employment and leisure, and no less important are the scarcity of elementary and secondary schools. KEYWORDS: Collective equipments, Social Interest Housing, Adequate Housing, PMCMV, Social Sustainability.